Investigating Community Problems Inside Indonesian National Parks: From Overview to Case Study at Sukamade Geoforest Coastal Area - Octastefani, Theresia; Wang, Hurng-Jyuhn (Universitas Muhammadiyah Sidoarjo, 2024)
This study explores the challenges encountered by residents within Indonesian national parks, focusing specifically on the local communities in the Sukamade Geoforest Coastal area of Meru Betiri National Park. Despite the recognized need for regional government and community involvement in park management, this research identifies a significant gap in effective community empowerment and management practices. Employing qualitative descriptive methods, including observations, interviews, and literature reviews, the study analyzes data using the Miles, Huberman, and Saldana interactive method, which includes data condensation, display, and verification. The findings reveal multifaceted issues faced by the Sukamade community, ranging from administrative and legal challenges to socio-cultural and environmental awareness problems. These results underline the necessity of integrating local communities into national park management to enhance environmental conservation efforts and community welfare, suggesting a reevaluation of current governance frameworks to address these complexities. Highlights: Lack of community empowerment hampers park management. Challenges include administrative, legal, socio-cultural, and environmental issues. Integrated management involving local communities is vital. Keywords: Indonesian National Parks, Community Involvement, Challenges, Multifaceted Issues